(untitled) (lectio difficilior, 2001)
The present article introduces to the history, the problems and prospects of gender archaeology, approaching the topic from the angle of the subject, the object and the context of gender-archaeological research. An analysis of the current state of archaeological interpretation and theory-building in the area of Palestine/Israel reveals a noticeable lack of gender-archaeological sensibility and reflection. Opening up to gender-specific questions could, however, improve the quality of the discipline at large regarding its hermeneutics, method, and practice. The heuristic possibilities of gender-archaeology are further exemplified by their application to the ‘Archaeology of Death’. It is specifically in this field ‑where these missing data would count most‑ that the archaeology of Palestine/Israel hardly applies new approaches and methods for the collection of data relevant to gender-specific research.